Suitability Assessment of Physical Properties of Common Edible and Inedible Oils as A Substitute for Conventional Mineral Transformer Oils in Nigeria - Omolola , Oladipo, Oluwamayowa (African Journal of Education,Science and Technology (AJEST), 2016)
As a result of climate change, the global trend is to find alternatives to petroleum-based products which are non-renewable in nature and hazardous to the environment in the event of spillage. Seed oils obtained from edible and inedible oils could be exploited as a possible alternative based on the fact that they are renewable and environmentally friendly. This research work aimed at investigating the potential of alternative sources of oil (natural esters) as a substitute for conventional mineral transformer oil. The physical properties of four different natural oils, which include palm oil supernatant, soybean, thevetia peruviana and jatropha oil, were studied in the course of the research. The laboratory analysis was carried out to determine specific gravity, flash point, fire point, pour point and kinematic viscosity. The materials used include oil samples, thermometer, Karl Fischer titrator, beakers, reagents, etc. The tests were carried out using basic laboratory procedures conforming to ASTM standards. Statistical analysis was carried out using SAS package and the means were separated using Duncan’s multiple range test. The result revealed that the specific gravity of all the natural oils except Palm oil supernatant were below the maximum stipulated value when compared to the conventional oil, while kinematic viscosity, flash, fire and pour points of the natural oils were below the recommended values as they were in unrefined states. Also, the widely acclaimed Soybean oil had values lesser than Jatropha oil, Palm oil supernatant and Thevetia peruviana oil thereby strengthening the potentials of these oils as substitutes for mineral oil if improved on. It could be concluded from this research work that natural oils in their unrefined states have lesser physical properties potential in substituting for mineral oils as transformer oil. It is therefore recommended that further studies should be carried out on improving the physical properties of these oils in order to strengthen their potential as substitute for mineral oil.